From the perspective of multi-theory model, factors influencing physical activity among community-dwelling older adults with type 2 diabetes in China: a mixed-methods study - Huai, Panpan; Zhang, Bo; Sun, Jingjing; Xu, Rui; Zhang, Linghui; Qiao, Xiao; Sun, Weili; Yang, Hui; Guo, Jinli; Su, Huancheng (Frontiers in Public Health, 2025)
AimTo examine the factors influencing physical activity among community-dwelling older adults with type 2 diabetes in China, and to provide a strong theoretical framework and empirical support for creating more individualized and scientific strategies for improving physical activity.MethodsThe text was analyzed by the innovative combination of traditional thematic analysis method and topic modeling (python machine learning) through the qualitative study, aiming to deeply explore the experiences and views of older adults with type 2 diabetes in the community regarding physical activity. Quantitative study adopted a cross-sectional survey to objectively and efficiently discover causal relationships among data. Finally, the results from the two different researches were compared to identify differences, similarities, and contradictions, enabling mutual verification and supplementation of the research findings and compensating for the limitations of a single research method, thereby obtaining the ultimate results.ResultsWe compared and integrated the qualitative and quantitative study results, and finally determined 11 topics, including 23 key factors, as the set of the study results of this study.ConclusionFrom the perspective of Multi-theory model, this study explored the related factors influencing the physical activity of older adults with type 2 diabetes in the community through a mixed-methods study. By comparing and integrating the results of qualitative and quantitative studies, we finally identified 11 topics, including 23 key factors, as the results of this study, such as “Focus on physical activity itself,” “The persistence of physical activity,” and “Traditional conception,” which were not mentioned in previous systematic literature search. These new discoveries provide a empirical support for creating more individualized and scientific strategies for improving physical activity behaviors among older adults with type 2 diabetes in the community.